2016
DOI: 10.1007/s13277-016-5274-9
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast activation protein alpha is expressed by transformed and stromal cells and is associated with mesenchymal features in glioblastoma

Abstract: Glioblastomas are deadly neoplasms resistant to current treatment modalities. Fibroblast activation protein (FAP) is a protease which is not expressed in most of the normal adult tissues but is characteristically present in the stroma of extracranial malignancies. FAP is considered a potential therapeutic target and is associated with a worse patient outcome in some cancers. The FAP localization in the glioma microenvironment and its relation to patient survival are unknown. By analyzing 56 gliomas and 15 non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 74 publications
10
81
0
Order By: Relevance
“…There was a wide intertumoral variability in the expression of both molecules, possibly reflecting their differential expression in individual molecular subtypes of glioblastoma (ref. 12 and our unpublished data) and our unpublished data. FAP immunopositivity was detectable by WB in most of the high-grade glioma samples, but was absent in the DPP-IV negative gliomas.…”
supporting
confidence: 59%
See 3 more Smart Citations
“…There was a wide intertumoral variability in the expression of both molecules, possibly reflecting their differential expression in individual molecular subtypes of glioblastoma (ref. 12 and our unpublished data) and our unpublished data. FAP immunopositivity was detectable by WB in most of the high-grade glioma samples, but was absent in the DPP-IV negative gliomas.…”
supporting
confidence: 59%
“…Both proteases are involved in the regulation of cell differentiation, adhesion and migration by their proteolytic activity and also non-hydrolytic interactions 9,10 . Our previous reports demonstrated that the expression DPP-IV and FAP is increased in glioblastomas 11,12 . The data on their pathogenetic role in brain tumors is limited-DPP-IV inhibits glioma cell growth, in large part independently of its enzymatic activity 13 , and FAP likely influences the interaction of glioma cells with the surrounding extracellular matrix (our unpublished results and ref.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Human cancer FAP expression is reported to correlate to higher tumor grade and worse survival across a worldwide range(11),like cancer on the breast, colon, stomach, etc(1215). Some studies(15, 16) indicated that FAP can induce EMT.…”
Section: Introductionmentioning
confidence: 99%